2001
DOI: 10.1530/rep.0.1210307
|View full text |Cite
|
Sign up to set email alerts
|

Novel method for intrafollicular pressure measurements in the rat ovary: increased intrafollicular pressure after hCG stimulation

Abstract: The ovulatory process in the rat comprises a period of about 12-15 h, from the time of the preovulatory LH surge to follicular rupture and extrusion of the oocyte. Follicular rupture is most likely caused, at least in part, by decreased tensile strength at the follicular apex due to degradation of collagen fibres of the extracellular matrix. It has been debated whether changes in intrafollicular pressure occur during the ovulatory process and whether such changes facilitate rupture of the follicle. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…This process is further amplified by the release of tumor necrosis factor-alpha (TNF-a) from the degraded ECM to promote collagenase production and apoptosis of ovarian epithelial cells (Curry & Smith 2006). The weakened cellular and ECM components at the apical region, along with pressure from the follicular fluid and increased vascular pressure, facilitate follicular rupture and expulsion of the oocyte into the periovarian space (Matousek et al 2001).…”
Section: Function: Signaling and Remodelingmentioning
confidence: 99%
“…This process is further amplified by the release of tumor necrosis factor-alpha (TNF-a) from the degraded ECM to promote collagenase production and apoptosis of ovarian epithelial cells (Curry & Smith 2006). The weakened cellular and ECM components at the apical region, along with pressure from the follicular fluid and increased vascular pressure, facilitate follicular rupture and expulsion of the oocyte into the periovarian space (Matousek et al 2001).…”
Section: Function: Signaling and Remodelingmentioning
confidence: 99%
“…Importantly, systemic administration of tezosentan prior to ovulation inhibits follicle rupture in superovulation-induced rats and mice [13], [22]. It has been previously proposed that follicular or ovarian contraction, which EDN2 may induce, serves as an ovulatory trigger for a follicle to rupture [23]. This idea is given credence by the presence of a smooth muscle network in the theca-interstitial layer of the ovary.…”
Section: Introductionmentioning
confidence: 98%
“…Using rats as the animal model, Matousek et al (2001) applied new techniques to the paradigm of changing intra-follicular pressure during the ovulatory cascade and we proposed that endothelin-2 (EDN2) was the final contractile signal facilitating ovulation (Ko et al 2006). Evidence suggests that these two seemingly intertwined processes are, however, independent factors within the ovulatory cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that these two seemingly intertwined processes are, however, independent factors within the ovulatory cascade. Changes in intra-follicular pressure are observed as early as midway through the periovulatory cascade (Matousek et al 2001), coincident with increases in factors affecting vascular permeability (Gómez et al 2003;Kitajima et al 2004;Miyabayashi et al 2005) and the array of proteolytic enzymes known to be integral to the breakdown of the extracellular matrix before ovulation (reviewed in Curry and Smith 2006). In contrast, expression of mRNA for Edn2 is only increased very late in the periovulatory period, ∼12 h after the induction of ovulation with hCG in the rat (Ko et al 2006), well after the first observed changes in intra-follicular pressure.…”
Section: Introductionmentioning
confidence: 99%